Application of Problem Based Learning Model to Student Learning Outcomes Students on Ecosystem Material - Sholikhah, Rizky Wahyu; Agustina, Lina (Universitas Muhammadiyah Surakarta, 2024)
Problem Based Learning (PBL) model in learning biology helps students in solving a problem, because with PBL students learn from problems or cases that exist around us, this can affect student learning outcomes. This study aims to determine the application of the Problem Based Learning model to student learning outcomes on ecosystem material. The research method used was experimental research with Post-test Only Control Group Design, the research was conducted in class X of one of the high schools in Pacitan Regency. Data collection techniques in the form of tests conducted at the end of treatment (post test) both control class and experimental class. The results showed that the application of the Problem Based Learning model on ecosystem material had an effect on learning outcomes where the t test results counted 6.066 > t table 3.218, meaning that there was an average difference learning outcomes in control and experimental classes. It can be concluded that there is an effect of using the Problem Based Learning (PBL) learning model on learning outcomes in ecosystem material.